ITGB4 Deficiency in Airway Epithelium Aggravates RSV Infection and Increases HDM Sensitivity - Du, Xizi; Yuan, Lin; Yao, Ye; Yang, Yu; Zhou, Kai; Wu, Xinyu; Wang, Leyuan; Qin, Ling; Li, Wenkai; Xiang, Yang; Qu, Xiangping; Liu, Huijun; et al. (Frontiers in Immunology, 2022)
Background The heterogeneity of RSV-infected pathology phenotype in early life is strongly associate with increased susceptibility of asthma in later life. However, the inner mechanism of this heterogeneity is still obscure. ITGB4 is a down-regulated adhesion molecular in the airway epithelia of asthma patients which may participate in the regulation of RSV infection related intracellular pathways. Object This study was designed to observed the involvement of ITGB4 in the process of RSV infection and the effect of ITGB4 deficiency on anti-RSV responses of airway epithelia. Results RSV infection caused a transient decrease of ITGB4 expression both in vitro and in vivo. Besides, ITGB4 deficiency induced not only exacerbated RSV infection, but also enhanced HDM sensitivity in later life. Moreover, IFN III (IFN-λ) was significantly suppressed during RSV infection in ITGB4 deficient airway epithelial cells. Furthermore, the suppression of IFN-λ were regulated by IRF-1 through the phosphorylation of EGFR in airway epithelial cells after RSV infection. Conclusion These results demonstrated the involvement of ITGB4 deficiency in the development of enhance RSV infection in early life and the increased HDM sensitivity in later life by down-regulation of IFN-λ through EGFR/IRF-1 pathway in airway epithelial cells.